Structural Changes in Institutional System for Economic Planning in Libya during the Period (1960 - 2012) - Al- Jaroushi, Ali Abd Alsalam; Arbab, Musab Mutasim Saeed (Journal of Economic, Administrative and Legal Sciences, 2021)
The current study aims to state the stages whereby the institutional system of the economic planning underwent in Libya, the structural changes that took place during the study period. The significance of the study lies in the clarification of the impact of the administrative instability and the structural changes of the planning departments on the effectiveness of the economic policies and development in Libya. The researcher employed the analytic –descriptive, and historical methods to collect the data, facts and to deduce the most important stages of the development of the institutional system of the economic planning in Libya. The study came up with several results which can be summarized as follows, the administrative instability, the non- effectiveness of the planning authorities, duality of powers and inability to diversify the income sources. The researcher has recommended the administrative improvement and development of the state institutions through the promotion of the effectiveness of the workers by intensive training, and ending the duality of powers.
Keywords: economic planning; Libyan economy; structural changes; economic policies